Epstein-Barr virus infection in patients with MOGAD - Maniscalco, Giorgia T; Dinoto, Alessandro; Foglia, Maria C; Di Battista, Maria E; Moreggia, Ornella; Di Giulio Cesare, Daniele; Williams, Michela; Rossi, Francesca W; Carta, Sara; Chiodega, Vanessa; Ferrari, Sergio; Viola, Assunta; et al. (Multiple sclerosis, 2025)
Epstein-Barr virus (EBV) infection increases the risk of having multiple sclerosis (MS). Data on adults with myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) are lacking. To compare EBV serological status in MOGAD versus MS. We measured antibodies to Epstein-Barr nuclear antigen (EBNA-1) and viral capsid antigen (VCA) antigens in 129 patients (MS = 74, MOGAD = 55) by chemiluminescence immunoassays. VCA-IgG were detected in 97.3% of MS and 96.4% of MOGAD cases, while EBNA-1-IgG in 97.3% of MS and 80% of MOGAD ( = 0.001). EBNA-1 ( < 0.001) and VCA ( = 0.03) antibodies levels were higher in MS patients. EBV antibodies are higher in MS versus MOGAD, suggesting a possible different role of EBV in the pathogenesis of the two conditions.